Attacks on Polish Bank Customers During the Pandemic: Cyberscams and the Role of Security Alerts - Wojciech Kaczmarczyk (Finanse i Prawo Finansowe)
The purpose of the article. The publication aims to determine the extent to which changes in the use of e-banking during the COVID-19 pandemic influenced the methods and scale of cyberscams in Europe (including Poland). Additionally, it seeks to assess whether Polish banks conducted a proper information policy and were able to practically implement the adopted solutions during the examined period.